2015
DOI: 10.1089/fpd.2014.1875
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and Pulsotypes Diversity of Listeria monocytogenes in a Beef-Processing Environment

Abstract: Utensils and equipment from meat-processing facilities are considered relevant cross-contamination points of Listeria monocytogenes to foods, demanding tracking studies to identify their specific origins, and predict proper control. The present study aimed to detect L. monocytogenes in a beef-processing facility, investigating the diversity of serotypes and pulsotypes in order to identify the possible contamination routes. Surface samples from knives (n=26), tables (n=78), and employees hands (n=74) were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…One clear indication that raw meat is a common source of the introduction of L. monocytogenes into more than one factory was the observation that subcluster B2 isolates, mainly found in the raw meat department used for cutting and marinating raw beef in factory M4, also were found on the raw side, but not in the high-risk zone, of factory M1. L. monocytogenes strains, including ST9 strains, have frequently been found to persist in meat slaughterhouses ( 5 , 6 , 15 , 50 56 ). Therefore, a common primary source of a certain L. monocytogenes strain present in more than one meat processing plant potentially could be one that persists in a slaughterhouse supplying raw meat to multiple processing plants.…”
Section: Discussionmentioning
confidence: 99%
“…One clear indication that raw meat is a common source of the introduction of L. monocytogenes into more than one factory was the observation that subcluster B2 isolates, mainly found in the raw meat department used for cutting and marinating raw beef in factory M4, also were found on the raw side, but not in the high-risk zone, of factory M1. L. monocytogenes strains, including ST9 strains, have frequently been found to persist in meat slaughterhouses ( 5 , 6 , 15 , 50 56 ). Therefore, a common primary source of a certain L. monocytogenes strain present in more than one meat processing plant potentially could be one that persists in a slaughterhouse supplying raw meat to multiple processing plants.…”
Section: Discussionmentioning
confidence: 99%
“…Listeriosis in humans is mostly associated with the consumption of contaminated food. Many studies reported that the contamination of food-processing facilities and associated environments is often the route by which foods become contaminated [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of virulence genes in L. monocytogenes isolates obtained from food and food processing facilities has already been described in a number of studies, demonstrating their relevance for the characterization of this pathogen's virulence potential (Lomonaco et al, 2012;Jamali et al, 2013;Camargo et al, 2015;Haubert et al, 2015;Silva et al, 2016). A large number of genes potentially involved in virulence have been recognized by Maury et al (2016).…”
Section: Discussionmentioning
confidence: 95%